2020
DOI: 10.3390/nu12113380
|View full text |Cite
|
Sign up to set email alerts
|

B Vitamins and Their Role in Immune Regulation and Cancer

Abstract: B group vitamins represent essential micronutrients for myriad metabolic and regulatory processes required for human health, serving as cofactors used by hundreds of enzymes that carry out essential functions such as energy metabolism, DNA and protein synthesis and other critical functions. B vitamins and their corresponding vitamers are universally essential for all cellular life forms, from bacteria to humans. Humans are unable to synthesize most B vitamins and are therefore dependent on their diet for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 141 publications
(162 reference statements)
1
109
0
1
Order By: Relevance
“…Another family of GM-derived metabolites found to have an important role in the HSCT context are riboflavin-based precursors. These metabolites are produced by a wide range of bacteria including E. coli , Staphylococcus aureus and Pseudomonas aeruginosa , and have a positive effect in expanding a particular T-cell subtype known as mucosal-associated invariant T cells (MAIT) [ 64 , 65 ]. In particular, MAIT cells respond to vitamin B2/B9–derived metabolites presented by MR1, an MHC class I–like molecule, producing IFN-g, IL-17, releasing cytotoxic granules and antibacterial products [ 66 ].…”
Section: Riboflavin (Vitamin B2)-derived Metabolitesmentioning
confidence: 99%
“…Another family of GM-derived metabolites found to have an important role in the HSCT context are riboflavin-based precursors. These metabolites are produced by a wide range of bacteria including E. coli , Staphylococcus aureus and Pseudomonas aeruginosa , and have a positive effect in expanding a particular T-cell subtype known as mucosal-associated invariant T cells (MAIT) [ 64 , 65 ]. In particular, MAIT cells respond to vitamin B2/B9–derived metabolites presented by MR1, an MHC class I–like molecule, producing IFN-g, IL-17, releasing cytotoxic granules and antibacterial products [ 66 ].…”
Section: Riboflavin (Vitamin B2)-derived Metabolitesmentioning
confidence: 99%
“…NAD plays critical roles in redox reactions, in which NAD and NADH are interconverted. NAD also functions as a substrate for sirtuins, NAD‐dependent protein deacetylases that connects transcriptional regulation to cellular energetics [ 91 ]. Dietary fiber and carbohydrates from host mucins undergo fermentative pathways to generate monosaccharides by bacterial polysaccharidases and/or glycosidases.…”
Section: Cancer‐promoting Bacteriamentioning
confidence: 99%
“…A deficiency of these vitamins from increased cellular demand or absorption defect leads to various physiological disruptions. Many, but not all, members of the gut microbiota are prototrophic for B vitamin synthesis ( Peterson et al, 2020 ). It has been suggested that auxotrophic human gut bacteria rely on B vitamin sharing within the GI microenvironment for survival, as humanized gnotobiotic mice supported B vitamin auxotroph survival for at least 4 weeks regardless of dietary vitamin intake ( Sharma et al, 2019 ).…”
Section: Microbiome-mediated Mechanisms and Impact On Homeostasismentioning
confidence: 99%
“…Human cells can also synthesize NAD via niacin-independent salvage pathways. In addition to its role in essential redox reactions, NAD plays a role in epigenetic enzyme regulation and genomic stability, as well as reactive oxygen species inhibition ( Peterson et al, 2020 ). Administration of niacin disrupts NF-κB signaling, leading to suppression of inflammatory cytokines; its effects have been investigated in the context of several human diseases, including atherosclerosis, fatty liver disease, and Parkinson’s disease ( Su et al, 2015 ; Peterson et al, 2020 ).…”
Section: Microbiome-mediated Mechanisms and Impact On Homeostasismentioning
confidence: 99%